(1371) قضيه الاقتصاد المصري الكبرى قصه الانتاج المصري في ظل الانفتاح الاقتصادي المشاكل والحلول من 1975 - 1982 The major issue of the Egyptian economy: The story of Egyptian production under economic liberalization – problems and solutions from 1975 to 1982 - سيد احمد البواب (معهد التخطيط القومي, 2026)
تناقش الدراسة "قضية الإنتاج" كأولوية قصوى لعلاج مشاكل الاقتصاد المصري، موضحةً أن فترة الانفتاح شهدت معدلات نمو حقيقية مرتفعة بلغت نحو 9.5% سنوياً، لكنه كان "نمواً مكلفاً" (pp. 1, 7, 10). فقد اعتمد هذا النمو بشكل أساسي على الموارد الطبيعية الناضبة (البترول وقناة السويس) وتحويلات المصريين بالخارج، وتزامن مع ارتفاع ضخم في الدين الخارجي وعجز ميزان المدفوعات، بالإضافة إلى وجود اختلال هيكلي حيث نمت قطاعات الخدمات والتجارة بمعدلات تفوق بكثير قطاعات الإنتاج السلعي كالزراعة والصناعة التي تراجعت مساهمتها في الاقتصاد. وتسلط الضوء على المعوقات التي واجهت القطاع العام، وأهمها سياسة التسعير الاجتماعي التي أدت لتباين الأسعار عن تكلفتها الاقتصادية، مما نتج عنه خسائر مالية وظهور السوق السوداء. كما يرصد البحث اتساع "الفجوة الغذائية" حيث أصبحت مصر تستورد أكثر من نصف احتياجاتها، مع انكماش الصادرات الزراعية التقليدية، وتوصي الدراسة بضرورة جعل الإنتاج السلعي العمود الفقري للتنمية، وفصل سياسة الدعم عن التسعير، والتحول من مرحلة "تصدير الفائض" إلى "الإنتاج من أجل التصدير" لضمان استمرارية النمو وتحسين مستوى المعيشة. The study discusses the "issue of production" as a top priority for addressing the problems of the Egyptian economy. It explains that the period of economic liberalization witnessed high real growth rates of approximately 9.5% annually, but this growth was "costly" (pp. 1, 7, 10). This growth relied primarily on depleting natural resources (oil and the Suez Canal) and remittances from Egyptians abroad. It coincided with a massive increase in external debt and a balance of payments deficit, in addition to a structural imbalance where the services and trade sectors grew at rates far exceeding those of commodity-producing sectors such as agriculture and industry, whose contribution to the economy declined. The study highlights the obstacles faced by the public sector, most notably the social pricing policy, which led to a discrepancy between prices and their economic cost, resulting in financial losses and the emergence of the black market. The research also notes the widening "food gap" as Egypt now imports more than half of its needs, with traditional agricultural exports shrinking. The study recommends making commodity production the backbone of development, separating subsidy policy from pricing, and shifting from "exporting surplus" to "production for export" to ensure continued growth and improve living standards.